2014
DOI: 10.1002/ijc.29056
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptor γ upregulates galectin‐9 and predicts prognosis in intestinal‐type gastric cancer

Abstract: The importance of PPARc (peroxisome proliferator-activated receptor c) in gastric cancer (GC) is unclear. We investigated the role of PPARc in GC cell lines and an animal model, and its prognostic significance of PPARc in GC patients. We controlled PPARc and galectin-9 expression by using siRNAs and lentiviral constructs. Interaction between PPARc and galectin-9 was evaluated using luciferase and chromatin immunoprecipitation assays. PPARc expression in GCs was determined by immunohistochemical staining of tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…In the present study, the downregulated DEGs were significantly enriched in ‘chemical carcinogenesis’, ‘metabolism of xeno-biotics by cytochrome P450’, ‘peroxisome’, ‘fatty acid degradation’ and ‘gastric acid secretion’. These results also coincided with the results of previous studies ( 23 – 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the downregulated DEGs were significantly enriched in ‘chemical carcinogenesis’, ‘metabolism of xeno-biotics by cytochrome P450’, ‘peroxisome’, ‘fatty acid degradation’ and ‘gastric acid secretion’. These results also coincided with the results of previous studies ( 23 – 27 ).…”
Section: Discussionsupporting
confidence: 93%
“…Rosiglitazone, a PPAR γ agonist was shown to inhibit hepatocellular carcinoma (32) , and gastric cancer cell growth (33). Also, troglitazone the other PPAR γ agonist has the same effect on prostate cancer cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…Though the roles of PPARγ in cancer therapy are debatable, accumulating evidence suggested that activation of PPARγ by agonists exerts an inhibitory effect on cancer cells [32]. For example, PPARγ agonists dramatically reduced cell growth of hepatocellular carcinoma [33], prostate cancer [34], and gastric cancer [35] via regulating the expression and blocking the oncogenic proteins. In our study, we found that PPARγ agonist RGZ had an ability to inhibit proliferation of esophageal cancer cells in time- and dose-dependent manners.…”
Section: Discussionmentioning
confidence: 99%